Study on sensory characteristics of paneer for process standardization from buffalo milk : Sensory characteristics of paneer - J. Badshah; Kumar, Sanjeev; Suryamani Kumar; B. K. Bharti; A. K. Jha (Indian Journal of Dairy Science, 2023)
Buffalo milk was utilized in a research project undertaken with the process variables for standardization of processes of manufacturing of paneer. The sensory evaluation study was described to have the effects of treatments on sensory scores for standardizing the manufacturing process. Effect of treatments on flavor score, and body and texture score were significant at P < 0.01 and P < 0.05, however, the effect of replication of sensory evaluations by Judges was non-significant. Effect of treatments on colour and appearance score was significant at P<0.05. It meant that at 95% level of confidence only the treatments of colour and appearance was significant i.e. different. Looking into the sensory scores and literature, it can be concluded that the buffalo milk of 6% milk fat and 9% SNF chilled in 1% NaCl solution was most suitable in regard of good body and texture of paneer at the preheating temperature of milk at 80-82°C.